2013
DOI: 10.1111/ijfs.12447
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring colour, volatiles in the headspace and enzyme activity to assess the quality of broccoli florets (Brassica oleracea L. italica cv. Bellstar and Legacy) during postharvest storage

Abstract: Summary The research objective was to study whether volatile organic compounds released in the headspace could be used to assess the broccoli quality (Brassica oleracea L. italica cv. Bellstar and Legacy) during postharvest storage (23 °C for 7 days) and correlated with colour change and the activity of peroxidase/POD, ascorbic acid oxidase/AAO and lipoxygenase/LOX. Volatile organic compounds were monitored using PTR‐MS. Methanol had the highest concentration compared with other volatiles released in the heads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 54 publications
(65 reference statements)
1
0
0
Order By: Relevance
“…Also in the study of Engel et al (2002), sulfurous compounds (e.g., dimethyl trisulfide) were observed in the volatile profile of priorly blanched cooked chopped cauliflower [ 2 ]. Furthermore, sulfurous compounds can be derived from the (enzymatic) decomposition of cysteines substituted with an S-compound as well as their sulfoxides (e.g., S-methyl-L-cysteine sulfoxide) by C-S lyases, which is in agreement with other studies in which dimethyl disulfide is the main reported compound derived from this pathway [ 27 , 30 , 68 , 69 , 70 ]. Additionally, dimethyl disulfide and dimethyl trisulfide were observed to be major and minor products derived from the thermal degradation of sulfur-containing amino acids [ 67 ].…”
Section: Resultssupporting
confidence: 89%
“…Also in the study of Engel et al (2002), sulfurous compounds (e.g., dimethyl trisulfide) were observed in the volatile profile of priorly blanched cooked chopped cauliflower [ 2 ]. Furthermore, sulfurous compounds can be derived from the (enzymatic) decomposition of cysteines substituted with an S-compound as well as their sulfoxides (e.g., S-methyl-L-cysteine sulfoxide) by C-S lyases, which is in agreement with other studies in which dimethyl disulfide is the main reported compound derived from this pathway [ 27 , 30 , 68 , 69 , 70 ]. Additionally, dimethyl disulfide and dimethyl trisulfide were observed to be major and minor products derived from the thermal degradation of sulfur-containing amino acids [ 67 ].…”
Section: Resultssupporting
confidence: 89%